Effect of Pressure on Microstructure of <111>‐Oriented β‐SiC Films: Research via Electron Backscatter Diffraction. Issue 12 (28th August 2015) - Zhang, Song; Xu, Qingfang; Sun, Qingyun; Zhu, Peipei; Tu, Rong; Hu, Zhiying; Han, Mingxu; Goto, Takashi; Zhang, Lianmeng; Yan, Jiasheng; Li, Shusen
Abstract : Scanning electron microscopy (SEM) and high‐resolution electron backscatter diffraction (EBSD) has been employed to study the microstructure development of <111 > ‐oriented β‐SiC films prepared by laser chemical vapor deposition (LCVD) with various total pressure ( P tot ). The Surface morphology of films evolved from pyramids with sixfold symmetry to needlelike structure by increasing the P tot . The EBSD results indicated that the higher P tot (800 Pa) led to the lower neighbor‐pair misorientation and large in‐plane domains in β‐SiC films.